2011
DOI: 10.1007/s00421-011-2066-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of warm footbath on arterial stiffness in healthy young and older women

Abstract: Acute systemic thermal therapy can improve arterial stiffness in both animals and humans. We examined and compared the effects of acute local thermal therapy (footbath) on an indicator of human arterial stiffness, cardio-ankle vascular index (CAVI), in 16 healthy young (29.4 ± 0.4 years) and 16 older (59.8 ± 1.7 years) women. Measurements were made at baseline (BL) and at 0 and 30 min after footbath in footbath trial, and at corresponding time points without footbath in control trial. In the footbath trial, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 37 publications
3
43
0
Order By: Relevance
“…Effects on human health of footbath have been investigated and confirmed since 1960s [2][3][4]. The local exposure to warm water would dilate the blood vessels underneath the skin and then increases the blood flow via blood capillaries and finally enhance the distal-proximal skin temperature gradient, leading to a transient improvement in the blood circulation [5,6], systemic arterial stiffness [7], and sleep quality [8][9][10]. In the recent years, the warm footbath has become a nursing approach for older people for its safe and convenience, compared to immersion of the whole body in warm water.…”
Section: Introductionmentioning
confidence: 99%
“…Effects on human health of footbath have been investigated and confirmed since 1960s [2][3][4]. The local exposure to warm water would dilate the blood vessels underneath the skin and then increases the blood flow via blood capillaries and finally enhance the distal-proximal skin temperature gradient, leading to a transient improvement in the blood circulation [5,6], systemic arterial stiffness [7], and sleep quality [8][9][10]. In the recent years, the warm footbath has become a nursing approach for older people for its safe and convenience, compared to immersion of the whole body in warm water.…”
Section: Introductionmentioning
confidence: 99%
“…; Hu et al . ). While the efficacy of thermal therapy on cardiovascular health has at this point been demonstrated by multiple studies, the underlying mechanisms are less understood.…”
mentioning
confidence: 97%
“…The literature has suggested that part of the mechanism by which heat therapy ameliorates cardiovascular health is through alleviation of arterial stiffness (Hu et al . ). Consequently, Brunt et al .…”
mentioning
confidence: 97%
See 2 more Smart Citations